2015
DOI: 10.1103/physrevd.92.126005
|View full text |Cite
|
Sign up to set email alerts
|

Information content inF(R)brane models with nonconstant curvature

Abstract: In this work we investigate the entropic information-measure in the context of braneworlds with non-constant curvature. The braneworld entropic information is studied for gravity modified by the squared of the Ricci scalar, besides the usual Einstein-Hilbert term. We showed that the minimum value of the brane configurational entropy provides a stricter bound on the parameter that is responsible for the F (R) model to differ from the Einstein-Hilbert standard one. Our results are moreover consistent to a negati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 34 publications
6
35
0
Order By: Relevance
“…This incoherentsecular situation was nicely explored in Ref. 47 , where different mechanisms responsible for irreversibility in QARs were classified: internal dissipation, which corresponds to the competition between cooling pathways that are optimized at different parameters, and heat leaks, a direct heat exchange between the work and cold baths.…”
Section: B Four-level Qar With Coherencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This incoherentsecular situation was nicely explored in Ref. 47 , where different mechanisms responsible for irreversibility in QARs were classified: internal dissipation, which corresponds to the competition between cooling pathways that are optimized at different parameters, and heat leaks, a direct heat exchange between the work and cold baths.…”
Section: B Four-level Qar With Coherencesmentioning
confidence: 99%
“…[43][44][45] . Recent studies on QARs looked at physical realizations 46 , the impact of internal leaks and dissipation 47 , and the roles of topology 48 , internal couplings 28 , and strong system-bath coupling effects 49 . Other questions of interest include the cooling performance of the QAR at maximum power 42,50,51 , and the behavior of its current fluctuations 52 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in braneworld scenarios it was shown that CE can be employed to demonstrate a high organizational degree in the structure of the system configuration for large values of a parameter of the sine-Gordon model [47]. The entropic information-measure in the context of f (R) braneworlds with non-constant curvature has also been studied [48].…”
Section: Introductionmentioning
confidence: 99%
“…The energy density is indeed suitable for defining the correspondent conditional entropy because it encodes more enhanced elements of the physical system. Of course, it is much more evident for spatially localized structures, as those described by lumps and kinks, and by an infinite set of one dimensional (non)topological defects [21][22][23][24][25][26][27][28][29]. For the energy density Fourier decomposed into components weighted by the modes k n , the normalized structure factor is constructed upon the collective coordinates as [3,4,11]…”
Section: Configurational Entropy In the Elementary Contextmentioning
confidence: 99%